Managing Conservations Value to Enhance Tourist Electronic Word of Mouth for Rural Tourism Destinations - Johannes Johannes; Deci Fachrosi (Universitas Hayam Wuruk Perbanas, 2022)
Over the past few years, Indonesia has made various efforts to increase tourist visits. This study aims to examine the effect of experiential marketing on conservation value, the effect of experiential marketing on e-WoM (electronic Word of Mouth), and the mediating effect of customer value on the relationship between experiential marketing and e-WoM in rural conservation destinations. Hence, a survey was conducted to 125 visitors with structured questions and used PLS to reveal the relationship between experiential marketing on e-Wom, where customer conservation value has a mediation function. Thus, customers’ conservation value will contribute to the marketing of rural tourism destinations. The results showed that experiential marketing positively and significantly affects conservation value, but it does not directly affect e-Wom unless mediated by customer conservation value. Therefore, this study suggests that destination managers and tourist guides maintain and continue improving the tourist experience and add conservation attributes to the destination. So, the tourist will comprehend the attributes through their online device. In doing so, they will be involved in marketing activities with e-WoM as the destination marketer’s partner.